PRODUCTIVITY OF GAMAL (Gliricidia sepium) AND INDIGOFERA (Indigofera zollingeriana) FORAGE ON DIFFERENT DOSAGE OF BIOORGANIC FERTILIZER - N. G. K., Roni; Lindawati, S. A. (Pastura; Vol 8 No 2 (2019): Pastura Vol. 8 No. 2 Tahun 2019, 2019)
This study aims to obtain a study of the productivity of Gliricidia sepium and Indigofera zollingeriana plants which are given various dosage of bioorganic fertilizer. This study used a completely randomized design of factorial patterns of two factors: the first factor was the type of plant (G = Gamal; I = Indigofera) and the second factor was the dosage of bioorganic fertilizer: D0 = without fertilizer; D1 = 5 tons ha-1; D2 = 10 tons ha-1; D3 = 15 tons ha-1; D4 = 20 tons ha-1; D5 = 25 tons ha-1; and D6 = 30 tons ha-1, so there are 14 treatment combinations. Each treatment was repeated three times so that it consisted of 42 experimental units. The variables observed were plant height, leaf number, stem diameter, leaf dry weight, stem dry weight, total herbage dry weight, amount of chlorophyll, ratio of dry weight of leaf / stems, and leaf area per pot. The results showed that the productivity of Indigofera zollingeriana significant higher than Gliricidia sepium. The application of bioorganic fertilizer significantly increased plant height, leaf number, dry weight leaf, stem dry weight, total forage dry weight, amount of chlorophyll, and leaf area per pot, and the highest yield at 30 tons/ha. Based on the results of the study it can be concluded that the productivity of Indigofera zollingeriana is higher than Gliricidia sepium, bioorganic fertilizer increased plant productivity with the highest yield at 30 tons ha-1, and interaction only occurs in the leaf area per pot. Keywords: Indigofera zollingeriana, Gliricidia sepium, dosage of fertilizer, bioorganic fertilizer